The Voluntary Inclusion of Forecasts in the MD&A Section of Annual Reports* - CLARKSON, PETER M.; KAO, JENNIFER L.; RICHARDSON, GORDON D. (Contemporary Accounting Research, 1994)
Abstract. In this study, we appeal to theories advanced by Darrough and Stoughton (1990) to enhance our understanding of why some firms may voluntarily include directional forecasts in their annual reports while others do not. The data are consistent with their predictions that a firm's disclosure policy reflects its concern for both financial market valuation and product market competition. We find that for “good news firms, the probability of forecasting is increasing in the financing requirements but decreasing in the threat of competitor entry. The converse holds for “bad news” firms. These results lend further empirical support to the observation that the familiar good news hypothesis tested in the management earnings forecast literature offers only a partial explanation for the decision to forecast. Interestingly, however, even after controlling for financial and product market considerations, an overall voluntary disclosure bias still exists in the data. The data also provide support for the OSC's concern about a voluntary disclosure bias. Only 17.5 percent of our sample forecasts represent revisions downward relative to the previous year's results. However, in contrast to the OSC's concern about a general lack of forward‐looking disclosures in annual reports, 35.9 percent of our sample firms include directional forecasts in their MD&A or elsewhere in the annual report.